2018
DOI: 10.35817/jpu.v1i1.6293
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH KUALITAS PELAYANAN TERHADAP PENINGKATAN PENERIMAAN RETRIBUSI DAERAH (Studi pada Dinas Perindustrian dan Perdagangan Kabupaten Konawe Selatan)

Abstract: Effect of Service Quality on Increasing Regional Retribution Receipts (Study on the Department of Industry and Trade of South Konawe Regency).The purpose of the study was to find out and analyze the effect of service quality on the reception of regional retribution, and analyze the significance of the effect of service quality on the receipt of regional retribution. This research is explanatory research using survey design. The population of this study amounted to 456 people, consisting of: elements of service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Adanya perbedaan kontribusi Pajak Daerah antara saat PPKM diperketat dan setelah PPKM diperlonggar adalah karena terjadi peningkatan realisasi penerimaan pajak daerah setelah aturan PPKM diperlonggar sebesar 37,75%. Hasil tersebut sesuai dengan penelitian yang dilakukan oleh (Fadilla & Wafiroh, 2022) (Sari, 2021) menunjukkan bahwa pandemi Covid-19 berdampak signifikan terhadap retribusi secara keseluruhan, yaitu terjadi penurunan pada beberapa jenis retribusi, namun beberapa jenis retribusi lainnya tidak terkena dampak dari adanya Covid-19 tersebut.…”
Section: Pembahasan Perbedaan Kontribusi Pajak Daerah DI Kota Surakar...unclassified
“…Adanya perbedaan kontribusi Pajak Daerah antara saat PPKM diperketat dan setelah PPKM diperlonggar adalah karena terjadi peningkatan realisasi penerimaan pajak daerah setelah aturan PPKM diperlonggar sebesar 37,75%. Hasil tersebut sesuai dengan penelitian yang dilakukan oleh (Fadilla & Wafiroh, 2022) (Sari, 2021) menunjukkan bahwa pandemi Covid-19 berdampak signifikan terhadap retribusi secara keseluruhan, yaitu terjadi penurunan pada beberapa jenis retribusi, namun beberapa jenis retribusi lainnya tidak terkena dampak dari adanya Covid-19 tersebut.…”
Section: Pembahasan Perbedaan Kontribusi Pajak Daerah DI Kota Surakar...unclassified
“…Moreover, in previous studies it was found that service quality has a positive and significant effect on income (Lestari, 2019). In addition, other studies have also found that service quality has a positive influence on regional revenue (Aslim, 2018). That is, in order to be able to increase income, it is also important to know how to deeply understand about consumer perceptions of the quality of the services provided by local MSME in Mataram today.…”
Section: Introductionmentioning
confidence: 99%